2018
DOI: 10.11114/jets.v6i6.3113
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects of Proprioceptive Neuromuscular Facilitation Stretching on Sports Performance: A Review

Abstract: The role of flexibility on athletic performance is going on to be studied both acutely and how it affects the performance in the long-term. It is important to understand the effects of various stretching types and define the most appropriate form in order to maximize the human movement and performance. Proprioceptive neuromuscular facilitation (PNF) stretching techniques are commonly used at athletic and clinic settings with the aim of optimizing motor performance and rehabilitation in order to increase range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
1
2
0
2
Order By: Relevance
“…The systematic review of Higgs and Winte [ 39 ] showed that flexibility training has a chronic beneficial effect on strength capacity, and a recommendation should be maintained to include flexibility exercise routines in parallel with strength training, as a way to obtain better strength gains. Subsequently, other studies found the same results [ 36 ], corroborating with our CT group, which resulted in greater strength gains when compared to the MT group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The systematic review of Higgs and Winte [ 39 ] showed that flexibility training has a chronic beneficial effect on strength capacity, and a recommendation should be maintained to include flexibility exercise routines in parallel with strength training, as a way to obtain better strength gains. Subsequently, other studies found the same results [ 36 ], corroborating with our CT group, which resulted in greater strength gains when compared to the MT group.…”
Section: Discussionsupporting
confidence: 90%
“…The most commonly cited capacity associated with flexibility in the literature is strength, mainly explosive strength (power) and maximum strength [ 35 ]. However, a common view of flexibility associated with strength is that stretching before a strength training session may reduce performance, and after the training session, may increase the risk of injury [ 35 , 36 ]. These data are from adults and athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the values obtained in the MT and MFT groups are higher than those presented in the literature. The study by Mitchell et al 33 reported a total score of 12. 2 points in a study with 97 older women with a mean age of 65.…”
Section: Discussionmentioning
confidence: 98%
“…32 No entanto, a visão da flexibilidade que vem aliada a força é sobre o efeito do alongamento antes de uma sessão de treinamento de força, que pode vir a reduzir o desempenho da mesma, ou depois da sessão de treinamento, que pode aumentar o risco de lesão. 32,33 Entretanto, nosso estudo mostrou como a força muscular pode ser aumentada com o desenvolvimento da capacidade de flexibilidade, o que pode indicar a importância de se incluir treinos de flexibilidade tanto quanto de força para essa população. A revisão sistemática de Higgs e Winter 34 mostrou que o treinamento de flexibilidade tem efeito crônico benéfico na capacidade de força, devendo ser mantida uma recomendação para incluir rotinas de exercícios de flexibilidade paralelamente ao treinamento de força, como forma de se obter melhores ganhos na força.…”
Section: Discussionunclassified
See 1 more Smart Citation